Assessment of Ultrasonic Noise Hazard in Workplaces Environment - ŚLIWIŃSKI, Antoni (Archives of Acoustics, 2013)
The hazard assessment of ultrasonic noise impact on human body at workplaces presents an open problem; it is not satisfactorily solved comparing the fund of knowledge and standard regulations estab- lished for the case of audible noise. Some research carried on in the Central Institute of Labour Protection – National Research Institute, Poland, are essential for elaboration reliable procedures for the assessment of ultrasonic noise hazard and they have to bring to modernization and creation the corresponding stan- dards in this field. In the presentation, some problems related to measurement procedures applied as well as to the interpretation of results essential for hazard assessment of ultrasonic noise impact on human body will be considered; in particular such cases where some procedures elaborated for audible noise assessment are being transferred to apply in the ultrasonic range without taking fully into account some specific aspects of the high frequency components of the noise.